Immunogenicity and Safety of a Measles-Mumps-Rubella Vaccine Administered as a First Dose to Children Aged 12 to 15 Months: A Phase III, Randomized, Noninferiority, Lot-to-Lot Consistency Study. (8th March 2019) - Klein, Nicola P; Abu-Elyazeed, Remon; Povey, Michael; Macias Parra, Mercedes; Diez-Domingo, Javier; Ahonen, Anitta; Korhonen, Tiina; Tinoco, Juan-Carlos; Weiner, Leonard; Marshall, Gary S; Silas, Peter E; Sarpong, Kwabena O; et al.
Abstract: Background: MMR II (M-M-R II [Merck & Co, Inc.]) is currently the only measles, mumps, and rubella (MMR) vaccine licensed in the United States. A second MMR vaccine would mitigate the potential risk of vaccine supply shortage or delay. In this study, we assessed the immunogenicity and safety of another MMR vaccine (MMR-RIT [Priorix, GlaxoSmithKline]) compared with those of the MMR II in 12- to 15-month-old children who received it as a first dose. Methods: In this phase III, observer-blinded, noninferiority, lot-to-lot consistency clinical trial (ClinicalTrials.gov identifier NCT01702428), 5003 healthy children were randomly assigned to receive 1 dose of MMR-RIT (1 of 3 production lots) or MMR II along with other age-recommended routine vaccines. We evaluated the immunogenicity of all vaccines in terms of antibody concentrations (by using an enzyme-linked immunosorbent assay or electrochemiluminescence assay) and/or seroresponse rates 43 days after vaccination. We also assessed the reactogenicity and safety of the vaccines. Results: Immunoresponses after vaccination with MMR-RIT were robust and noninferior to those after vaccination with the MMR II. Immunogenicity of the 3 production lots of MMR-RIT was consistent; more than 97% of the children had a seroresponse to MMR components. The coadministered vaccines elicited similar immunoresponses in the MMR-RIT and MMR II groups. Both MMR vaccines resulted in comparable reactogenicity profiles, and no safety concerns were detected. Conclusions: If licensed, the MMR-RIT could provide a valid option for the prevention of measles, mumps, and rubella in children in the United States and would reduce potential risks of a vaccine shortage. Abstract : When compared with the MMR II vaccine (M-M-R-II) currently available in the United States, a first dose of MMR-RIT (Priorix) given to 1-year-old children elicited robust immunoresponses and raised no safety concerns.